A Comparison of Violence Victimization and Polyvictimization Experiences Among Sexual Minority and Heterosexual Adolescents and Young Adults. Issue 11 (June 2021) - Schwab-Reese, Laura M.; Currie, Dustin; Mishra, Aura A.; Peek-Asa, Corinne
Despite recent civil rights advances for sexual minority communities in the United States, disparities in violence victimization have increased in recent years. Polyvictimization, the experience of multiple types of violence, is common in the United States and may result in mental and physical health consequences above and beyond single-type victimization. However, disparities in polyvictimization among sexual minority young people remain understudied. The purpose of this article was to determine whether there were disparities in monovictimization and polyvictimization among sexual minority young people compared with their heterosexual peers. Data for this article were from The National Longitudinal Study of Adolescent to Adult Health, a nationally representative cohort study started in 1994. Participants reported their experiences with eight types of violence across child abuse, criminal assault, intimate partner violence (IPV), and sexual assault domains. We categorized individuals with no violence victimization as nonvictims, individuals with one form of victimization as monovictims, and individuals with multiple types of victimization as polyvictims. We then compared experiences of each type of victimization and overall monovictimization and polyvictimization by sexual orientation ( n = 9, 828). Among females, the proportions of individuals experiencing victimization by sexual orientation were significantly different for all forms of violence. Among males, criminal assault, IPV resulting in injury, and nonphysically and physically forced sexual assault differed by sexual orientation. Compared with 100% heterosexual peers, individuals who were mostly heterosexual had significantly increased odds of monovictimization and polyvictimization compared with no victimization. Bisexual individuals had significantly increased odds of polyvictimiztion, and mostly/100% homosexual individuals had significantly increased odds of monovictimization. Multiple victimization experiences may be a pathway to lifetime health disparities, so our findings may explain many of the health disparities experienced in sexual minority communities. It will be critical to develop and evaluate intervention and prevention programs to eliminate these disparities.